2007
DOI: 10.1097/01.sla.0000254418.90192.59
|View full text |Cite
|
Sign up to set email alerts
|

Primary Breast Lymphoma

Abstract: Mastectomy offers no benefit in the treatment of PBL. Nodal status predicts outcome and guides optimal use of radiation and chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(82 citation statements)
references
References 27 publications
0
78
0
2
Order By: Relevance
“…More than 80% of PBL are B-cell lymphomas (DLBCL), mostly CD20+. The most frequent histopathologic types are: diffuse large B-cell lymphoma (DLBCL) which accounts for up to 50% of all PBL, follicular lymphoma (FL)-15%, MALT lymphoma-12.2%, Burkitt's lymphoma (BL) and Burkittlike lymphoma-10.3% [10]. Other histological types of PBL include marginal zone lymphoma (MZL), small lymphocyticlymphoma (SLL), and anaplastic large cell lymphoma (ALCL).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More than 80% of PBL are B-cell lymphomas (DLBCL), mostly CD20+. The most frequent histopathologic types are: diffuse large B-cell lymphoma (DLBCL) which accounts for up to 50% of all PBL, follicular lymphoma (FL)-15%, MALT lymphoma-12.2%, Burkitt's lymphoma (BL) and Burkittlike lymphoma-10.3% [10]. Other histological types of PBL include marginal zone lymphoma (MZL), small lymphocyticlymphoma (SLL), and anaplastic large cell lymphoma (ALCL).…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analyses also confirm that the early stage and use of RT are favourable prognostic factors. Jennings et al [10] in a Cox regression model, analyzing the tumour size and node status, revealed that the node status is the best single predictor of survival. The most common chemotherapy agents used in PBL have been those in the CHOP regimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical and radiological presentation of both PBL and SBL may be similar to breast carcinoma but their treatments differ radically [5,7,14,15,16]. In fact, up until recently, surgery was considered the gold standard in the management of breast lymphomas [25,26], but recent studies have reported that mastectomy offered no benefit in the treatment of PBL and SBL and that therapy based on chemotherapy and/or radiotherapy provided better results in terms of survival and recurrence rates [17]. From this perspective, the cytological diagnosis of PBL and SBL can be extremely valuable for their management.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, intramammary reactive lymph node, sclerosing lobulitis, PBL and SBL do not necessarily require surgical excision, which would have a solely diagnostic value [5,7,14,15,16]. Therefore, an accurate, preoperative cytological diagnosis could allow proper and specific therapeutic procedures [17]. …”
Section: Introductionmentioning
confidence: 99%